Analysis of the Quintilii's Villa Bronzes by Spectroscopy Techniques. (26th February 2014) - Stranges, Fabio; La Russa, Mauro; Oliva, Antonino; Galli, Giuliana
Abstract : The aim of this work is the characterization, with different diagnostic tests, of three fragments of bronze artefacts recovered from the Villa of the Quintilii (located in the south of Rome). In particular, the sample alloys were investigated by different chemical and morphological analysis. Firstly, an analysis of the alloy, implemented through the electronic spectroscopy, was taken to discriminate the bronze morphology and its elemental composition. Subsequently, a surface analysis was realized by molecular spectroscopy to identify the alteration patinas on surfaces (such as bronze disease). Two diagnostic techniques are used for the alloy analysis: scanning electron microscopy (SEM) connected to the EDX spectroscopy (to study the morphology and alloy composition) and Auger electron spectroscopy (AES) (to identify the oxidation state of each element). Moreover, for the study of surface patinas, IR and Raman spectroscopies were implemented. All studies were performed on the "as received" samples, covered by a thin layer of excavated soil and on samples processed in an aqueous solution of sulphuric acid (10%), to remove patinas and alterations.